Penerapan New Normal Sebagai Strategi Pemulihan Covid-19 Di Indonesia - Elizabeth Amelia Permata Sari (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The COVID-19 outbreak of the SARS-CoV-2 virus has surprised us with its rapid transmission and deadly complications. Therefore, movement restrictions have been put in place to contain this pandemic. Recently, there has been increasing pressure to restart and revive social and economic sectors and to allow people to return to work. This should be well planned before movement restrictions are lifted. Therefore, this study aims to review the implementation of the new normal as a Covid-19 recovery strategy in Indonesia. First, the social and economic sectors must be opened in stages by prioritizing occupational safety and health rather than economic recovery. Meanwhile, WHO recommendations regarding social distancing and personal hygiene must be adjusted and become the new normal. Therefore, the government and local governments must develop a soft landing approach based on WHO recommendations. Furthermore, the community must be involved and empowered to do their part in preventing the spread of COVID-19. From the new normal recommendations, people can continue their daily routines, while reducing the transmission of COVID-19. However, medical possibilities were not considered when drafting this new normal and procedure. Society must adapt and embrace the new normal to control, reduce and prevent the spread of COVID-19, as it has been with us for a long time.